Ultrastructural evaluation of renal tubular epithelial cells of the rats’ kidneys after anthracyclines therapy - Pedrycz, Agnieszka; Siermontowski, Piotr; Polz, Dorota; Kocki, Janusz; Puchalska-Kosiecz, Agnieszka (Current Problems of Psychiatry, 2011)
Anthracyclines are antineooplastic antibiotics. In the present study Adriamycin (ADR) induced apoptosis of renal tubular epithelial cells. The study material consisted of Wistar female rats, which were divided into 2 control and 2 experimental groups. Experimental groups: rats treated with a single intraperitoneal dose of Adriamycin - 5 mg/kg body weight and decapitated after 4 (gr. I) and 7 (gr. III) weeks. Control groups: rats treated with a single intraperitoneal dose of 0.9% NaCl- 0.5 ml and decapitated after 4 (gr. II) and 7 (gr. IV) weeks. Semi-thin - 0.5-0.7 μm and ultrathin - 60 nm slideswere prepared from left kidneys segments taken from the rats. Under electron and light microscope using semi-thin slides we observed apoptosis of kidney’ cells. In experimental groups a large number of cells showed damaged pyknotic nuclei of reduced perimeter, changed shape and dark blue-black in semi-thin specimens. Naked pyknotic nuclei were visible in the renal tubular lumen. Those changes increased in the time of the experiment.